News media and public perceptions of police misconduct: Does racial empathy matter? - Baranauskas, Andrew J. (Criminal justice studies, 2023)
High-profile instances of police violence, including the killings of George Floyd and Breonna Taylor, have received immense attention in the news media and brought public attention to police use of force and racial bias. This study examines the connection between news media consumption and public perceptions of police misconduct. It also explores the role of racial empathy, a positive out-group attitude, in mediating this relationship. Analyses of nationally representative survey data indicate that those who view online news sites and those who use Twitter are more likely to believe that police treat White people better than they treat Black people. The political bias of the news site also matters, as those who view right-leaning sites are less likely to believe that police use more force than necessary and act in a biased manner. Racial empathy plays a mediating role in the relationship between viewing news sites and perceptions of police misconduct. Implications for research and policy are discussed.